2022
DOI: 10.1097/mlr.0000000000001723
|View full text |Cite
|
Sign up to set email alerts
|

Using Administrative Data to Examine Telemedicine Usage Among Medicaid Beneficiaries During the Coronavirus Disease 2019 Pandemic

Abstract: Background: The coronavirus disease 2019 (COVID-19) pandemic necessitated the replacement of in-person physician consultations with telemedicine. During the pandemic, Medicaid covered the cost of telemedicine visits. Objectives: The aim was to measure the adoption of telemedicine during the pandemic. We focus on key patient subgroups including those with chronic conditions, those living in urban versus rural areas, and different age groups. Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 33 publications
2
9
0
Order By: Relevance
“…Telehealth offset over half of their in-person visit decline, highlighting the large residual post-PHE health care deficit for beneficiaries with chronic disease. Findings mirror literature documenting expanded telehealth chronic disease management post-PHE without a net visit increase providing reassurance that telehealth will not induce unnecessary utilization . In tandem, HSI expansion is unlikely to promote preventive care among healthy younger adults.…”
Section: Discussionmentioning
confidence: 53%
“…Telehealth offset over half of their in-person visit decline, highlighting the large residual post-PHE health care deficit for beneficiaries with chronic disease. Findings mirror literature documenting expanded telehealth chronic disease management post-PHE without a net visit increase providing reassurance that telehealth will not induce unnecessary utilization . In tandem, HSI expansion is unlikely to promote preventive care among healthy younger adults.…”
Section: Discussionmentioning
confidence: 53%
“…Given the qualifications for Medicaid in Florida, this finding is reasonable as people in lower income positions are associated with less resources and less access to telehealth. Research suggested that chronic disease management via telehealth and in-person care provide similar clinical outcomes, yet the lack of in-person options did not encourage telehealth use [17,29,30]. The pandemic decreased the options for people in vulnerable communities to receive care and adversely affected chronic disease management [17].…”
Section: Chronic Disease Managementmentioning
confidence: 99%
“…Research suggested that chronic disease management via telehealth and in-person care provide similar clinical outcomes, yet the lack of in-person options did not encourage telehealth use [17,29,30]. The pandemic decreased the options for people in vulnerable communities to receive care and adversely affected chronic disease management [17]. Chudasama et al (2020) reported that 67% of providers perceived that the pandemic had a moderate to severe effect on chronic disease management; 45% of healthcare professionals offered only telephone support, 35% provided telephone and in-person, and 14% maintained only in-person care [15].…”
Section: Chronic Disease Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies from early in the COVID-19 pandemic found less use of telemedicine visits and in fewer video telemedicine visits (than audio-only visits) among patients who were low-income, non-English-speaking, and older age. 12,13,[16][17][18][19][20] To our knowledge, few studies have examined how telemedicine use, and its modalities, has evolved. 5 If telemedicine is to remain a common and important approach to health care delivery, it is necessary to understand who is using the technology successfully and why, and, conversely, uncover barriers in access.…”
Section: Introductionmentioning
confidence: 99%